Buffering of blood pressure variability by the renin-angiotensin system in the conscious dog - Just, Armin; Kirchheim, Hartmut; Ehmke, Heimo (The journal of physiology, 1998)
1 The renin-angiotensin system (RAS) participates in the compensation of major blood pressure disturbances such as haemorrhage and is involved in the tonic long-term (> 1 day) maintenance of mean arterial blood pressure (MABP). Since its contribution to the short-term (< 1 h) buffering of normal blood pressure variability is not known, this was investigated in resting conscious dogs. 2 The regulatory efficiency and the response time of the RAS were studied by an acute step reduction of renal artery pressure to 70 mmHg for 1 h using a suprarenal aortic cuff. After a delay of at least 100 s, MABP rose exponentially by 22 ± 5 mmHg in normal dogs (n= 4), by 6 ± 3 mmHg after angiotensin converting enzyme (ACE) inhibition (n= 4), and by 25 ± 5 mmHg after ganglionic blockade (n= 4). MABP returned to control after release of the cuff with similar time courses. The time constants of the MABP responses were in the range of 20 min. Thus, possible feedback oscillations of the RAS would be expected around 0.0025 Hz (1/(4 × 100 s)); a buffering effect would be possible below this frequency. 3 Blood pressure variability was investigated by spectral analysis of MABP from 3.75 h recordings in the frequency ranges of 0.002-0.003 Hz (feedback oscillations) and below 0.002 Hz (buffering effect). 4 ACE inhibition (n= 7) decreased MABP by 11 ± 2 mmHg (P < 0.05), but in both frequency ranges integrated spectral density was not affected. ACE inhibition also failed to significantly change spectral density in either of the two frequency ranges under the following conditions: (1) during ganglionic blockade (n= 7), (2) during a low-sodium diet (except for a very slight elevation below 0.002 Hz) (n= 7), and (3) when the fall of MABP induced by ACE inhibition was compensated by an angiotensin II infusion (n= 7). 5 It is concluded that in spite of its high regulatory efficiency with an adequate response time the RAS does not directly contribute to the short-term buffering of blood pressure variability, nor does it give rise to feedback oscillations under normal resting conditions. Even if the RAS is stimulated by sodium restriction its contribution to short-term blood pressure buffering is only marginal.